An integrated approach to posterior anchorage preparation and incisor torque compensation in premolar extraction cases using clear aligners - Ruyue Qiang; Junjie Wu; Jie Gao; Haiwen Chen; Jianing Xu; Zuolin Jin; Yanning Ma (BMC Oral Health)
Abstract Background In clear aligner treatment (CAT), closure of the premolar space is achieved by reducing aligner length. Posterior anchorage preparation is effective in preserving molar angulation; however, the resulting distal tipping can contribute to anterior anchorage loss. This study aims to identify an approach that balances anterior torque compensation with posterior anchorage preparation in CAT. Methods Two finite element models were developed to simulate en-masse incisor retraction using clear aligners (CAs). Model 1 simulated first premolar extraction cases, while Model 2 simulated second premolar extraction cases. In Step I, only distal tipping was applied to the posterior teeth as an anchorage preparation strategy. In Step II, a positive torque of 0.08 degrees was introduced to the incisors to simulate torque compensation in a single orthodontic step. Results In Model 1, the maxillary lateral incisor and mandibular central incisor tipped further lingually compared to cases without posterior anchorage preparation. The posterior terminal teeth showed a tendency to tip mesially in Step I, which was partially reduced with anterior torque compensation in Step II. In Model 2, all incisors had a stronger tendency to tip lingually in Step I. Molar anchorage control improved with incisor torque compensation of 0.08 degrees. Tipping was more pronounced in the maxillary arches compared to the mandibular arches. Posterior anchorage loss was greater in Model 2, while Model 1 showed more pronounced anchorage loss in anterior teeth. Conclusions Posterior anchorage preparation alone increases the risk of anterior anchorage loss. Combining this approach with incisor torque compensation helps distribute the anchorage burden more effectively. As an advanced approach, anterior and posterior anchorage management should be strategically coordinated and adapted to the number of orthodontic steps required in premolar extraction cases treated with CAs. Clinical trial number Not applicable.